Cost of Disease Progression in Patients with Chronic Lymphocytic Leukemia, Acute Myeloid Leukemia, and Non‐Hodgkin's Lymphoma. (26th February 2019) - Reyes, Carolina; Engel‐Nitz, Nicole M.; DaCosta Byfield, Stacey; Ravelo, Arliene; Ogale, Sarika; Bancroft, Tim; Anderson, Amy; Chen, May; Matasar, Matthew
Abstract: Introduction: To reduce health care costs and improve care, payers and physician groups are switching to quality‐based and episodic or bundled‐care models. Disease progression and associated costs may affect these models, particularly if such programs do not account for differences in disease severity and progression risk within the cohort. This study estimated the incremental cost of disease progression in patients diagnosed with chronic lymphoid leukemia (CLL), acute myeloid leukemia (AML), and non‐Hodgkin's lymphoma (NHL) and compared costs among patients with and without progression. Methods: This was a retrospective study using U.S. administrative claims data from commercial and Medicare Advantage health care enrollees with evidence of CLL, AML, and NHL and systemic antineoplastic agent use from July 1, 2006 to August 31, 2014. Outcome measures included disease progression, 12‐month health care costs, and 3‐year cumulative predictive health care costs. Results: Of 1, 056 patients with CLL, 514 patients with AML, and 7, 601 patients with NHL, 31.1% of patients with CLL, 63.8% of those with AML, and 36.9% of those with NHL had evidence of disease progression. Among patients with CLL and NHL, adjusted and unadjusted health care costs were significantly higher among progressors versus nonprogressors. Per‐patient‐per‐month costs, accounting for variable follow‐up time, were almost twice as high among progressors versus nonprogressors in patients with CLL, AML, and NHL. In each of the three cancer types, the longer disease progression was delayed, the lower the health care costs. Conclusion: Progression of CLL, AML, and NHL was associated with higher health care costs over a 12‐month period. Delaying cancer progression resulted in a substantial cost reduction in patients with all three cancer types. Implications for Practice: Data on the rates and incremental health care costs of disease progression in patients with hematologic malignancies are lacking. This study estimated the incremental costs of disease progression in patients diagnosed with chronic lymphocytic leukemia, acute myeloid leukemia, and non‐Hodgkin's lymphoma and compared health care costs in patients with and without evidence of disease progression in a real‐world population. The data obtained in this study will assist future studies in quantifying the cost impact of decreased progression rates and will inform payers and physician groups about setting rates for episode and bundled payment programs. Abstract : This article provides estimates of the incremental cost of disease progression in patients diagnosed with chronic lymphocytic leukemia, acute myeloid leukemia, or non‐Hodgkin lymphoma and compares costs among patients with and without evidence of disease progression in a real‐world population.